Sensitivity‐Based Calibration of the Soil and Water Assessment Tool for Hydrologic Cycle Simulation in the Cong Watershed, Vietnam. (1st August 2015) - Anh, Nguyen Viet; Fukuda, Shinji; Hiramatsu, Kazuaki; Harada, Masayoshi
ABSTRACT: : For better water resources management in quality and quantity, an accurate model is needed for simulating the hydrologic cycle and water quality dynamics at a watershed scale. In this study, a semi‐distributed hydrologic model, the Soil and Water Assessment Tool (SWAT), was applied for hydrologic cycle assessment in the Cong Watershed, Vietnam. After model‐output and accuracy‐based sensitivity analyses were conducted without and with observation data, respectively, model parameters were calibrated and validated using meteorological and runoff data observed between 1961 and 1975. Model performance in annual, monthly, and daily flow simulations was assessed using the Nash–Sutcliffe Efficiency coefficient and the coefficient of determination ( R 2 ). As a result, the accuracy‐based sensitivity analysis better identified the key parameters, as compared to the model output‐based sensitivity analysis, resulting in better flow simulations in the Cong River. The calibrated model performed well in hydrologic cycle simulations in the Cong Watershed, suggesting the applicability of the SWAT model.